2014
DOI: 10.1002/ajmg.a.36778
|View full text |Cite
|
Sign up to set email alerts
|

Co‐occurrence of non‐mosaic trisomy 22 and inherited balanced t(4;6)(q33;q23.3) in a liveborn female: Case report and review of the literature

Abstract: Trisomy 22 is the third most common autosomal trisomy occurring in about 0.4% of all clinically recognized pregnancies. Complete non-mosaic trisomy 22 is extremely rare in live births. Most affected children die before one year of age. To date, only 29 liveborn cases have been reported and none has carried an additional genetic lesion. In this report, we describe the clinical presentation, cytogenetic, and cytogenomic findings in a liveborn female with complete non-mosaic trisomy 22 as well as a paternally inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Trisomy 22, in its complete or mosaic form, has an estimated incidence of up to 3–5% in spontaneous abortions [ 29 ]. While complete trisomy 22 is often non-compatible with life, leading to death in utero or shortly after birth [ 30 ], mosaic forms may survive through pregnancy and thrive in the postnatal life.…”
Section: Resultsmentioning
confidence: 99%
“…Trisomy 22, in its complete or mosaic form, has an estimated incidence of up to 3–5% in spontaneous abortions [ 29 ]. While complete trisomy 22 is often non-compatible with life, leading to death in utero or shortly after birth [ 30 ], mosaic forms may survive through pregnancy and thrive in the postnatal life.…”
Section: Resultsmentioning
confidence: 99%
“…Data is sparse regarding the overall ascertainment of fetal echocardiography leading to a diagnosis of aneuploidy, and there are few or no studies regarding fetuses with aneuploidy assessed by other means, and their subsequent echocardiographic findings (Pavlicek et al, 2019;Tuuli et al, 2009). In addition to the expanded prenatal diagnosis of aneuploidy syndromes with frequent CHDs, postnatal diagnosis of the most severe CHDs in CCHD newborn screening programs has grown rapidly worldwide (Bakker et al, 2019;Liberman et al, 2014;Oster et al, 2016 Smallhorn, & Freedom, 1990Wylie et al, 1994Lin et al, 2007Polli et al, 2014Kosiv, Gossett, Bai, & Collins, 2017Domingo, Carey, Eckhauser, Wilkes, & Menon, 2019Van Praagh et al, 1989Musewe et al, 1990Balderston, Shaffer, Washington, & Sondheimer, 1990Baty et al, 1994Crider, Olney, & Cragan, 2008Savva, Walker, & Morris, 2010Kosiv et al, 2017Abdelgadir, Nowaczyk, & Li, 2013Kehinde et al, 2014Bergstrom et al, 2016Pfitzer et al, 2018;Freeman et al, 2008Lange, Guenther, Busch, Hess, & Schreiber, 2007de Graaf et al, 2015 Prevalence of syndrome per 10,000 livebirths Abbreviations: AVSD, atrioventricular septal defect; BAV, bicuspid aortic valve; CHD, congenital heart defect; ETA, elongation of the transverse aorta; HLHS, hypoplastic left heart syndrome; LB, livebirth; PLSVC, persistent left superior vena cava; TAPVC, total anomalous pulmonary venous connection. disability, and high mortality.…”
Section: Chd Diagnosis and Management Across The Lifespanmentioning
confidence: 99%
“…Complete trisomy 22 typically leads to neonatal death (mean survival 4 days of life), with the maximum reported age of 3 years (Heinrich et al, 2012). A review of live-born patients with complete trisomy 22 noted that 92% (24/26) had CHDs (Kehinde et al, 2014). A review of the literature identified septal defects (Kontomanolis, Pandya, & Limperis, 2010;Ma, Ouyang, Hao, Zhao, et al, 2018;McPherson & Stetka, 1990;Naicker & Aldous, 2014), conotruncal anomalies (Stratton et al, 1993;Tinkle, Walker, Blough-Pfau, Saal, & Hopkin, 2003;Xu et al, 2019), aortic arch anomalies (Bacino et al, 1995), hypoplastic right heart (Bacino et al, 1995), and complex CHDs (Bacino et al, 1995;Tonni, Ventura, Pattacini, Bonasoni, & Ferrari, 2012).…”
Section: Trisomy 22mentioning
confidence: 99%
“…Trisomy 22 is a rare condition. Three cases of trisomy 22 and HPE has been reported (Fahmi, Schmerler, & Hutcheon, 1994; Isada, Bolan, Larsen, & Kent, 1990; Kehinde et al, 2014). One case of trisomy 16 has been associated with HPE, Petracchi et al in their study of 13,883 prenatal diagnoses, found 1 case of trisomy 16 presenting with holoprosencephaly.…”
Section: Syndromes Associated With Molecular Diagnosesmentioning
confidence: 99%